Does lagophthalmos change on lying supine after upper eyelid platinum segment chain loading?. (3rd September 2021) - Ullrich, Katja; Dolz-Güerri, Fernando; Neville, Catriona; Kannan, Ruben; Nduka, Charles; Litwin, Andre; Malhotra, Raman
ABSTRACT: Background: Facial nerve palsy (FNP) often significantly affects blink. Platinum segment chains (PSC) improve lagophthalmos, however, debate exists as to the effectiveness of weights when the patient lies supine. Methods: Prospective case series of patients with FNP following PSC insertion. Lagophthalmos on blink, gentle and forced closure was observed in the seated position, lying flat supine at 0 degrees, lying supine with one pillow underneath the head and lying on the side, with the non-facial palsy side to the pillow. This side was chosen to account for the effect that the pillow may have on lagophthalmos. Results: Twenty eyes with PSC for facial palsy related lagophthalmos were assessed in 19 patients. Clinically, 12 out of the 20 eyes had no change in lagophthalmos on gentle closure when sitting up compared to supine (no pillow). The remaining 8 eyes had an increase of lagophthalmos of mean 2.3 mm (range 1–6 mm) when supine. There was no statistical difference in the amount of lagophthalmos between sitting up and lying flat with no pillow on gentle closure ( P value = .0804) and blink ( P value = .1567). About 50% of patients have ongoing requirements for evening lubricating ointment application but only one patient in our cohort experienced morning ocular symptoms. No patient was taping their eyelids. Conclusion: In our study, the prevalence of lagophthalmos increasing on gentle closure when supine is 40%. Statistically, there is no difference between gentle closure in the sitting and supine position.